(untitled) (AmeriQuests)
President Donald Trump has suggested and supported a law, called the RAISE (Reforming American Immigration for a Strong Economy) Act, to allow legal immigration status to those who meet a narrow set of qualifications and accumulate points under those criteria. What is problematic is how few people would meet the criteria wherein a third of the points require large monetary investments, Nobel laureate status, and Olympic medals. In a country predicated on eliminating a meritocracy or system of monetary power, this seems to undermine American values.